Oral human papillomavirus infections in Zambian Rural and Urban residents-a community cross-sectional study - Chrispinus Hakimu Mumena; Schifra Uwamungu; Göran Kjeller; Bengt Hasséus; Maria Andersson; Daniel Giglio (BMC Oral Health)
Abstract Background How common it is with the presence of human papillomavirus (HPV) in the healthy and diseased oral cavity is largely unknown for Africans. In this cross-sectional study we assessed the prevalence of oral HPV and the risk factors associated with HPV contraction including sexual practice in the urban and rural Zambian population. Methods Urban (N = 188) and rural (N = 211) Zambian adults aged 21 years and older living in Ndola and Mansa, respectively, were interviewed about demographical data, oral and coital sexual history and tobacco and alcohol use. Participants were orally examined and underwent a buccal swab test for 12 high-risk HPVs (HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 59) and two low-risk HPVs (HPV6 and 11) with real-time PCR. Results Alcohol consumption was higher in urban participants than rural participants, i.e., 34.1% and 16.6%, respectively, consumed alcohol once a week or more (p = 0.001). Ever-smokers constituted 38.8% of urban and 32.2% of rural participants (p = 0.363). Engaging in orogenital sex was uncommon, however, more common in urban than rural participants (13.3% and 4.3%, respectively, p = 0.003). Only three participants were positive for HPV (HPV16, 35, and 45, respectively). Conclusions Urban participants displayed higher sexual risk behaviour than rural participants. However, the prevalence of oral HPV infection in Zambia was low, which contrasts to the high incidence of cervical cancer reported for the country.